2022
DOI: 10.1097/sap.0000000000003252
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Adjuvant Radiation and the Lymphedema Index

Abstract: Background Immediate lymphaticovenular bypass (immediate lymphatic reconstruction [ILR]) at the time of axillary lymph node dissection has emerged as a preventative paradigm to decrease the incidence of breast cancer–related lymphedema in high-risk patients. These patients are often treated with adjuvant therapies, including radiation. Bioimpedance spectroscopy is a validated tool for trending breast cancer–related lymphedema and identifying subclinical disease. Lymphedema Index (LDEX) values are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In our experience, patients who developed BCRL despite ILR were significantly more likely to be of an obese BMI at the time of surgery. The only additional significant difference between groups was the rate of adjuvant radiation therapy, a known risk factor for the development of lymphedema, which we have previously published upon 15 . However, further multivariate analysis demonstrated that there is a significant effect of BMI on the risk for BCRL independent of adjuvant radiation (OR 2.6 [1.2–5.5], P = 0.01).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…In our experience, patients who developed BCRL despite ILR were significantly more likely to be of an obese BMI at the time of surgery. The only additional significant difference between groups was the rate of adjuvant radiation therapy, a known risk factor for the development of lymphedema, which we have previously published upon 15 . However, further multivariate analysis demonstrated that there is a significant effect of BMI on the risk for BCRL independent of adjuvant radiation (OR 2.6 [1.2–5.5], P = 0.01).…”
Section: Discussionmentioning
confidence: 87%
“…The only additional significant difference between groups was the rate of adjuvant radiation therapy, a known risk factor for the development of lymphedema, which we have previously published upon. 15 However, further multivariate analysis demonstrated that there is a significant effect of BMI on the risk for BCRL independent of adjuvant radiation (OR 2.6 [1.2-5.5], P = 0.01). Given the baseline increased risk of developing BCRL with an obese BMI, our results may be further explained by additional genetic and cellular factors contributing to obesity and development of BCRL.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations